The value of G-CSF in women experienced at least one implantation failure: a systematic review and meta-analysis - Su, Qing; Pan, Zhuo; Yin, Rong; Li, Xuemei (Frontiers in Endocrinology, 2024)
What are the effects of different administration dosages and timing of granulocyte colony-stimulating factor (G-CSF) for women experienced at least one implantation failure?Findings: Ten RCTs evaluating the effect of different administration dosages and timing of G-CSF for women with at least one implantation failure were included. The present study demonstrated that G-CSF improved pregnancy outcomes. More specifically, >150μg of G-CSF treatment increased clinical pregnancy rate (CPR), implantation rate (IR), and biochemical pregnancy rate (BPR), while ≤150μg of G-CSF treatment improved miscarriage rate (MR) and live birth rate (LBR). In addition, G-CSF administration on the day of embryo transfer (ET) could increase CPR, but not on the day of ovum pickup (OPU) or human chorionic gonadotropin (HCG) injection.Meaning: Based on the meta-analysis, G-CSF could improve pregnancy outcomes, and the administration dosage and timing influence the effect size.